TABOOS AND MYTHS REGARDING BREASTFEEDING PRACTICES IN PREGNANT POPULATION: Breastfeeding Practices - Ibrar, Faiza; Khursheed, Naila; Qamar, Saima; Masud, Atikka; Ifthikhar, Bushra; Gul, Seema (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the taboos and myths regarding breastfeeding practices in our pregnant population.Study Design: Cross-sectional study.Place and Duration of Study: Obstetrics and Gynecology Department, Fauji Foundation Hospital, Rawalpindi Pakistan, from May to Oct 2018.Methodology: A total of 100 pregnant women attending antenatal clinics were included in the study using non-probability purposive sampling technique. Taboos and myths regarding breast feeding practices were determined using self-administered questionnaire on 2-point Likert scale (1=agree & 2=disagree).Results: A total of 100 pregnant women participated in the study. Mean parity was 2.89 ± 1.75 and gravidity was 4.17 ± 2.04. Most of the mothers (90%) were house wives and received information regarding breast feeding from family members (81%). Mothers were aware of the nutritious value of breast milk as compared to formula milk. However, there were myths that were not evidence based. These include: breasts sag with breast feeding (48%), it is not necessary to breast feed the baby during night time (43%), breast milk alone was not sufficient to satisfy the child (51%), small size breast produce insufficient milk (27%).Conclusion: Participants of this study are aware of the importance of breast feeding. However, there are certain taboos and myths prevailing in our population which are not proven scientifically.